The induction and effects of Substance P and its receptor in human immune cells and neurons: potential relevance in multiple sclerosis - Vilisaar, Janek (2012)
INTRODUCTION: Substance P (SP) has well-established roles in neurogenic inflammation and pain transmission, however recently, a number of SP immunomodulatory effects have been shown. In this thesis SP and its neurokinin-1-receptor (NK1R) role in autoimmune inflammation was investigated with an applicability to multiple sclerosis (MS). In the four experimental chapters the role of SP and its receptor was studied in human immune cells and neurons with a focus on the relationship with Th17 and Th1 pathways as the main pro-inflammatory arms in autoimmune pathology.